A Distinction between the Role of Precursor and Activated Forms of Clotting Factors in the Genesis of Stasis Thrombi - Wessler, S; Yin, E. T; Gaston, L. W; Nicol, Iona (Thrombosis and Haemostasis, 1967)
1. In vivo studies in rabbits have shown that the liver diminishes the thrombo-genicity of infused human serum.2. In vitro rabbit liver perfusions with human serum have demonstrated the loss of serum thrombogenicity within 5 min after the onset of the perfusion. Associated with this loss of thrombotic capacity is a marked decrease in the activation product (AP) and labile factor IX (PPA) activity in the infused serum.3. The liver appears to have the capacity to discriminate between circulating activated clotting activities such as AP and PPA and inactive procoagulants such as stable or genuine factor IX, factor VII and factor X. The latter are not cleared from the circulation by the liver.4. These studies provide some insight into the mechanism whereby circulating activated clotting activities and retarded blood flow predispose to thrombosis.